PENGARUH SMALL SIDED GAME DALAM MENINGKATKAN KAPASITAS AEROBIK PEMAIN BOLA VOLI PUTRI STKIP MUHAMMADIYAH KUNINGAN - Pitri Nurpaijah; Wahidi, Ribut; Budi, Budi (Journal of Physical Education and Sport Science, 2023)
Pitri Nurpaijah (NIM: 182223089), with the title "INFLUENCE OF SMALL SIDED GAMES IN INCREASING AEROBIC CAPACITY OF WOMEN'S VOLUTION BALL PLAYERS STKIP MUHAMMADIYAH KUNINGAN". This research is an experimental study and data collection techniques using One Group Pretest-Posttest with a population of 12 volleyball players STKIP Muhammadiyah Kuningan, using a 2.4km test instrument. The research method uses quantitative research methods, this data analysis technique uses the Normality Test and Homogeneity Test, the normality test of this data uses the Kolmogorov Smirnov test with a significant value for the pretest data 0.042 and for the posttest data 0.017 greater than 0.05 then the data is normally distributed. The significant value for Levene statistic is 0.010 > 0.05, then it is normally distributed. Furthermore, the calculated t value obtained is 9,039. Research subjects Students who take part in the Women's Volleyball UKM STKIP Muhammadiyah Kuningan.